Diffuse large B-cell lymphoma in a South African cohort with a high HIV prevalence: an analysis by cell-oforigin, Epstein-Barr virus infection and survival - Cassim, Sumaiya (Department of Clinical Laboratory Sciences, 2022)
Introduction: Diffuse large B-cell lymphoma, not otherwise specified (DLBCL NOS) is subdivided according to the cell-of-origin (COO) classification into germinal centre B-cell (GCB) and activated B-cell (ABC) subtypes, each with different molecular profiles and clinical behaviour. This study aims to describe the pattern of the COO subtypes, the proportion of Epstein-Barr virus (EBV) co-infection, and their influence on survival outcomes in a setting of high HIV prevalence. Materials and Methods: This retrospective cohort study included patients diagnosed with de novo DLBCL NOS at our tertiary academic centre in Cape Town, South Africa over a 14-year period. Immunohistochemical stains were performed for COO classification, according to the Hans algorithm. Tumour EBV co-infection was established by EBV-encoded ribonucleic acid in situ hybridisation (EBER-ISH) staining. The effect of the COO subtypes and EBV co-infection on overall survival were described by means of univariate, bivariate and multivariate analyses. Results: A total of 181 patients with DLBCL NOS were included, which comprised 131 HIV-uninfected and 50 HIV-infected patients. There was an equal distribution of GCB and ABC subtypes in the HIV-infected and HIV-uninfected groups. EBV co-infection was detected in 16% of the HIV-infected cases and in 7% of the HIV-uninfected cases (p=0.09). There was no significant difference in the incidence of EBV co-infection between the GCB and ABC subtypes (p=0.67). HIV-infected patients with CD4≥150 cells/mm3 had similar survival to HIV-uninfected patients (p=0.005). Multivariate regression analysis showed that in the HIVinfected group with marked immunosuppression (CD4 <150 cells/mm3), there was significantly poorer overall survival compared to the HIV-uninfected group (HR 2.4, 95% CI 1.3–4.1). There were no statistically significant differences in overall survival by DLBCL COO subtype. Conclusions: There was no difference in the proportion of DLBCL COO subtypes, regardless of HIV status. EBV co-infection was more common in the HIV-infected group, but less than described in the literature. Unexpectedly, there were no significant differences in survival outcomes between the GCB and ABC subtypes. Higher CD4 counts in the HIV-infected group had good survival outcomes, while lower CD4 counts predicted adverse survival outcomes. Further research is needed to explore the genetic mutational landscape of HIVassociated DLBCL.